Exaggerated sympathetic and pressor responses to handgrip exercise in older hypertensive humans: role of the muscle metaboreflex - Delaney, Erin P.; Greaney, Jody L.; Edwards, David G.; Rose, William C.; Fadel, Paul J.; Farquhar, William B. (American journal of physiology. Heart and circulatory physiology, 2010)
Recent animal studies have reported that exercise pressor reflex (EPR)-mediated increases in blood pressure are exaggerated in hypertensive (HTN) rodents. Whether these findings can be extended to human hypertension remains unclear. Mean arterial pressure (MAP), muscle sympathetic nerve activity (MSNA), and venous metabolites were measured in normotensive (NTN; n = 23; 60 ± 1 yr) and HTN ( n = 15; 63 ± 1 yr) subjects at baseline, and during static handgrip at 30 and 40% maximal voluntary contraction (MVC) followed by a period of postexercise ischemia (PEI) to isolate the metabolic component of the EPR. Changes in MAP from baseline were augmented in HTN subjects during both 30 and 40% MVC handgrip ( P < 0.05 for both), and these group differences were maintained during PEI (30% PEI trial: Δ15 ± 2 NTN vs. Δ19 ± 2 HTN mmHg; 40% PEI trial: Δ16 ± 1 NTN vs. Δ23 ± 2 HTN mmHg; P < 0.05 for both). Similarly, in HTN subjects, MSNA burst frequency was greater during 30 and 40% MVC handgrip ( P < 0.05 for both), and these differences were maintained during PEI [30% PEI trial: 35 ± 2 (NTN) vs. 44 ± 2 (HTN) bursts/min; 40% PEI trial: 36 ± 2 (NTN) vs. 48 ± 2 (HTN) bursts/min; P < 0.05 for both]. No group differences in metabolites were observed. MAP and MSNA responses to a cold pressor test were not different between groups, suggesting no group differences in generalized sympathetic responsiveness. In summary, compared with NTN subjects, HTN adults exhibit exaggerated sympathetic and pressor responses to handgrip exercise that are maintained during PEI, indicating that activation of the metabolic component of the EPR is augmented in older HTN humans.